2015
DOI: 10.1080/15222055.2015.1066472
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Frequency and Rate Effects on Growth and Physiology of Juvenile Genetically Improved Farmed Nile Tilapia

Abstract: To establish an effective feeding regime for the aquaculture of genetically improved farmed Nile Tilapia Oreochromis niloticus (GIFT), this experiment investigated the effects of feeding frequency and daily ration on the growth of GIFT fry (initial weight, ca. 0.85 g). A factorial experiment design of two feeding frequencies (2 and 3 meals/d) and five feeding rates (2, 4, 6, 8, and 10% body weight per day [BW/d]) was carried out over 70 d with three replicates for each treatment. At the end of the experiment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 34 publications
7
24
2
2
Order By: Relevance
“…In the present study also weight gain, SGR, FCR and PER was reduced when feeding ration was increased beyond 3% BW/day (Table 1). This is in agreement with the observations of Huang et al (2015) in genetically improved tilapia wherein growth response reached maximum with increase in feeding ration, but decreased further on increase of feeding ration and it was due to nutrient level reaching intolerable level. Similar observations were also reported for juvenile grass carp by Du et al (2006).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study also weight gain, SGR, FCR and PER was reduced when feeding ration was increased beyond 3% BW/day (Table 1). This is in agreement with the observations of Huang et al (2015) in genetically improved tilapia wherein growth response reached maximum with increase in feeding ration, but decreased further on increase of feeding ration and it was due to nutrient level reaching intolerable level. Similar observations were also reported for juvenile grass carp by Du et al (2006).…”
Section: Resultssupporting
confidence: 92%
“…Weight gain and SGR of C. auratus increased significantly (P<0.05) with the feeding ration from 2% BW/ Wet weight gain (g) day to 3% BW/day and feeding frequency from 1 meal/day to 4 meals/day (Table 1). Results of the present study showed agreement with those of Huang et al (2015) and Luo et al (2015) wherein weight gain and SGR increased with increase in feeding ration and feeding frequency. The highest weight gain and SGR was obtained in fishes fed 3% BW/day at a feeding frequency of 4 meals/day during the present study.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…It has been well documented that suboptimal feeding leads to a poor nutritional status of fish including sturgeon (Deng et al, ; Huang et al, ; Lee, Huller, Fangue, Fandel, & Hung, ; De Riu et al, ; Zheng, Deng, Riu, Oniello, & Hung, ). This was also observed in lake sturgeon fed the suboptimal feeding rates (<1.0% BW/day) from this study, wherein these fish displayed low liver to body index (HSI), decreased fasting blood glucose levels and whole‐body lipid contents.…”
Section: Discussionmentioning
confidence: 99%